Comparing Integrated and Disciplinary Clinical Training Patterns for Dental Interns: Advantages, Disadvantages, and Effect on Students' Self‐Confidence. Issue 3 (1st March 2016) - Wu, Junrong; Feng, Xiaoli; Chen, Aijie; Zhang, Yanli; Liu, Qi; Shao, Longquan
Abstract : In China, the five‐year program of undergraduate education for stomatology consists of four years of lecture courses and one year of internship focused on clinical training. Dental schools provide this clinical training either in their own clinics (referred to as the one‐stage pattern because all forms of practice are completed together) or by placing students in external clinics usually at non‐affiliated hospitals (referred to as the three‐stage program because the three primary areas are taught separately). The aims of this study were to investigate differences in teaching effect between the one‐stage and the three‐stage patterns and to evaluate advantages and disadvantages of the two patterns. A three‐section, 31‐item questionnaire was designed to assess basic and clinic information about the interns' training and their self‐confidence in performing clinical procedures. The survey was administered to graduates who finished the fifth‐year internship in 2012–14. Of the 356 individuals invited to participate, 303 graduates who spent their intern years in 43 academic dental institutions returned completed surveys (response rate of 85%). The one‐stage group (n=121) reported longer independent operation time than the three‐stage group (n=182) (p<0.01). No significant difference was found between the groups for assessment of clinic infrastructure (p=0.121). The interns were most confident in oral hygiene instruction and scale and polish (overall median=5), but showed low confidence in rubber dam placement and four other procedures (overall median=2). The one‐stage group rated their confidence level higher than the three‐stage group on comprehensive skills such as arranging appointments and managing patients and procedures needing long treatment periods such as molar endodontics. The three‐stage group showed higher confidence on more specialized procedures such as surgical extractions and suturing. This study found that both of the two intern patterns had advantages and shortcomings in clinical training in various procedures. Combining the two could be a way to improve clinical education in China.